Subsequent Actions Engendered by the Absence of an Immediate Response to the Proposal in Mandarin Mundane Talk - Hao, Quanxi; Guo, Hui; Li, Chuntao; Yang, Shuai (Frontiers in Psychology, 2022)
When there is no immediate response after a proposal, and normally the silence is longer than 0.2s, the proposer would take subsequent actions to pursue a preferred response or mobilize at least an articulated one from the recipient. These actions modulate the prior deontic stance embedded in the original proposal into four trends: (1) maintaining the prior deontic stance with a self-repair or by seeking confirmation; (2) making the prior deontic stance more tentative by making a revised other-attentiveness proposal, providing an account, pursuing with a tag question, or requesting with an intimate address term; (3) making the prior deontic stance more decisive by making a further arrangement (for the original proposal), closing the local sequence or providing a candidate unwillingness account (for the recipient’s potential rejection); and (4) cancelling the prior deontic stance by doing a counter-like action. Additionally, these trends inherently embody a decisive-to-tentative gradient. This paper would penetrate into the phenomena occurring in Mandarin mundane talk with the methodology of Conversation Analysis to uncover the underflow of deontic stance.